Learning Effectiveness of ESD-Oriented Natural and Social Science Projects in Realizing Pancasila Student Profiles for Vocational High School Students - Latifah, Nur; Syaipul Hayat, Muhammad; Khoiri, Nur (KnE Social Sciences, 2024)
The objective of this research is to assess the effectiveness of ESD-oriented Natural and Social Sciences Project (IPAS Project) learning in achieving the Pancasila student profile of critical reasoning dimensions. This research employs a quasi-experimental approach with a pre-test and post-test control group design. The research sample consisted of two groups: the experimental class and the control class. According to Ennis, a validated critical thinking test serves as the measurement instrument to assess the increase in students’ critical reasoning abilities after learning intervention. An observation sheet is also utilized to observe the Pancasila student profile in the critical reasoning dimension. The results of the research show that ESD-oriented natural and social science project learning is moderately effective in achieving the Pancasila student profile regarding the critical reasoning dimension. The average N-Gain score for the experimental class (ESD-oriented learning) is 63.51%, falling within the moderately effective and average category. The average N-Gain score for the control class (non-ESD-oriented learning) is 56.05%. Based on the observations of Pancasila student profiles of students engaging in ESD-oriented natural and social science project learning in the critical reasoning dimension, it is evident that some students in all elements of critical reasoning can attain the developing category as anticipated, according to the phase. These findings indicate that the ESD approach in learning natural and social science projects can effectively realize the Pancasila student profile of critical reasoning dimensions. Keywords: IPAS project (natural and social sciences project), ESD (education for sustainable development), Pancasila student profile; critical reasoning